Estimation of Gini index within pre-specified error bound - Bhargab Chattopadhyay; Shyamal Krishna De (Econometrics, 2016)
Gini index is a widely used measure of economic inequality. This article develops a theory and methodology for constructing a confidence interval for Gini index with a specified confidence coefficient and a specified width without assuming any specific distribution of the data. Fixed sample size methods cannot simultaneously achieve both specified confidence coefficient and fixed width. We develop a purely sequential procedure for interval estimation of Gini index with a specified confidence coefficient and a specified margin of error. Optimality properties of the proposed method, namely first order asymptotic efficiency and asymptotic consistency properties are proved under mild moment assumptions of the distribution of the data.
Keywords: C13; C14; C40; C44; 330; distribution-free method; fixed width confidence interval; Gini index; sample size planning; U-statistics